First Year Survey of Arthropods in California Hemp - Britt, Kadie E.; Meierotto, Sarah; Morelos, Victoria; Wilson, Houston (Frontiers in Agronomy, 2022)
Hemp is a newly (re)introduced crop to United States and California agriculture. A study was initiated in the summer of 2021 to survey the arthropods present in hemp in two regions of California: Fresno County in the Central Valley and Ventura County along the Central Coast. Eight hemp plots were sampled every two weeks from August to mid-October using a combination of D-vac samples, leaf collections, and visual observations. All samples were processed and ultimately recorded as the total number of specimens collected per morphospecies across all sampling dates, further broken down to express the number of specimens collected from the Central Valley and the Central Coast. Findings from this survey provide baseline information on the arthropod species present in California hemp. This survey will be repeated and expanded in future growing seasons.